P07 | DISRUPTED GUT-VASCULAR BARRIER AND INFLAMMATORY REMODELING IN MNGIE: A SPATIAL TRANSCRIPTOMIC AND HISTOLOGICAL STUDY (European Journal of Histochemistry)
Mitochondrial Neurogastrointestinal Encephalomyopathy (MNGIE) is a rare genetic disorder caused by loss-of-function mutations in the enzyme thymidine phosphorylase (TP). TP deficiency disrupts nucleoside metabolism, leading to progressive and fatal mitochondrial dysfunction. Although liver transplantation restores TP activity and improves survival, it does not reverse gastrointestinal damage, which includes fibrosis, hypoxia, muscle layer disorganization, and sometimes life-threatening haemorrhage. TP plays a critical role in early blood vessel development, and its absence in MNGIE is associated with impaired vascularization, marked by the preponderance of very small (<50 µm) and more fragile vessels. To study vascular alterations, we applied Visium CytAssist spatial transcriptomics to full-thickness jejunal samples from two MNGIE patients and two controls. Despite limited tissue availability, this approach revealed distinct layer-specific transcriptional profiles, highlighting signatures of aberrant vascular remodelling. Among all the analysed tissue layers, considering specifically the vascular compartment, 68 differentially expressed genes (DEGs) were identified with a p<0.001. Among these, we observed increased expression of genes involved in inflammatory and bacterial responses, including IGHA1, DEFA6, REG3A, DEFA5, JCHAIN, OLFM4, IGKC, REG1A, LYZ, DMBT1, and APOC3. This observation is consistent with the quantification of mast cells in full-thickness jejunal tissue. Compared to controls, MNGIE samples showed a 68% increase in mast cell count in the mucosa (p=0.0115), an 82% increase in the submucosa (p=0.0076), and a 98% increase in the neuromuscular layer (p=0.0017). The submucosa itself contained 48 DEGs (p<0.001), mirroring the vascular signature of increased inflammatory and bacterial response. Collectively, these data, together with jejunal histology, suggest impaired gut-vascular barrier integrity and increased permeability. Ongoing analyses of circulating biomarkers and dedicated permeability assays are underway to validate the molecular evidence presented in this preliminary study.